2007
DOI: 10.1190/1.2431635
|View full text |Cite
|
Sign up to set email alerts
|

Stacking of surface waves

Abstract: The seismic surface wave method (SWM) is a powerful means of characterizing near-surface structures. Although the SWM consists of only three steps (data acquisition, determination of dispersion curves, and inversion), it is important to take considerable care with the second step, determination of the dispersion curves. This step is usually completed by spectral analysis of surface waves (SASW) or multichannel analysis of surface waves (MASW). However, neither method is ideal, as each has its advantages and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…Several shots are considered for each position of the moving window and the dispersion curve is extracted from each shot. Stacking in the f-k domain is then applied to improve the S/N ratio (Neducza, 2007) and a new search is run on the stacked f-k gather. The dispersion curve that is then inverted is the one retrieved from the stacked data, while the ones obtained from single shot records are used to estimate the experimental uncertainties.…”
Section: Active Surface Wave Datamentioning
confidence: 99%
“…Several shots are considered for each position of the moving window and the dispersion curve is extracted from each shot. Stacking in the f-k domain is then applied to improve the S/N ratio (Neducza, 2007) and a new search is run on the stacked f-k gather. The dispersion curve that is then inverted is the one retrieved from the stacked data, while the ones obtained from single shot records are used to estimate the experimental uncertainties.…”
Section: Active Surface Wave Datamentioning
confidence: 99%
“…7 New Perspectives: Interferometry and Tomography for Surveys in 2D/3D Sites Current trends in surface wave methods include attempts to evaluate lateral variations. Often this is pursued with a collection of adjacent surface wave surveys (Tian et al 2003;Bohlen et al 2004;Neducza 2007). Reinterpretation of seismic reflection/refraction datasets provides a cost effective approach in this respect (Grandjean and Bitri 2006;Socco et al 2009).…”
Section: Recommendationsmentioning
confidence: 99%
“…Considering seismic reflection data, several examples presented in literature have shown that surface-wave dispersion curves can be extracted conveniently from seismic reflection records (Park et al, 2005;Neducza, 2007). Because acquisition of reflection data usually is not optimized for surface waves, we first must assess whether the data fulfill the quality requirements for surface-wave analysis.…”
Section: Synergiesmentioning
confidence: 99%